The 4′-Hydroxyl Group of Resveratrol Is Functionally Important for Direct Activation of PPARα - Takizawa, Yoshie; Nakata, Rieko; Fukuhara, Kiyoshi; Yamashita, Hiroshi; Kubodera, Hideo; Inoue, Hiroyasu (PLOS ONE, 2015)
Long-term moderate consumption of red wine is associated with a reduced risk of developing lifestyle-related diseases such as cardiovascular disease and cancer. Therefore, resveratrol, a constituent of grapes and various other plants, has attracted substantial interest. This study focused on one molecular target of resveratrol, the peroxisome proliferator activated receptor α (PPARα). Our previous study in mice showed that resveratrol-mediated protection of the brain against stroke requires activation of PPARα; however, the molecular mechanisms involved in this process remain unknown. Here, we evaluated the chemical basis of the resveratrol-mediated activation of PPARα by performing a docking mode simulation and examining the structure-activity relationships of various polyphenols. The results of experiments using the crystal structure of the PPARα ligand-binding domain and an analysis of the activation of PPARα by a resveratrol analog 4-phenylazophenol (4-PAP) in vivo indicate that the 4′-hydroxyl group of resveratrol is critical for the direct activation of PPARα. Activation of PPARα by 5 μM resveratrol was enhanced by rolipram, an inhibitor of phosphodiesterase (PDE) and forskolin, an activator of adenylate cyclase. We also found that resveratrol has a higher PDE inhibitory activity (IC50 = 19 μM) than resveratrol analogs trans-4-hydroxystilbene and 4-PAP (IC50 = 27-28 μM), both of which has only 4′-hydroxyl group, indicating that this 4′-hydroxyl group of resveratrol is not sufficient for the inhibition of PDE. This result is consistent with that 10 μM resveratrol has a higher agonistic activity of PPARα than these analogs, suggesting that there is a feedforward activation loop of PPARα by resveratrol, which may be involved in the long-term effects of resveratrol in vivo.